Dependencies of Personal Vehicle Sales on the Financial Support of their Sales - Kampf, Rudolf; Vochozka, Marek; Lejsková, Pavla; Cmíral, Tomáš (Kaunas University of Technology, 2014)
The article describes the dependence of the sales of BMW vehicles in the Czech republic on the financial support of those sales. The current state of sales support of selected BMW models in the Czech Republic is desribed as is the level of dependence of those sales on the scale of support which analyzed using regression models. In addition, the future development of sales, of selected BMW vehicles is given. The article was written as the partial outcome of research carried out in 2012.
Závislosti prodeje osobních vozidel na finanční podpoře jejich prodeje
Keywords: sales support; communication mix; regression analysis; dependence; podpora prodeje; komunikační mix; regresní analýza; závislost